PEMBERDAYAAN UMKM ARZZAM TAILOR MELALUI PENCATATAN KEUANGAN SEDERHANA DAN STRATEGI PEMASARAN DIGITAL - Putri Nabila Haerunisa; Nur Afni Chelya Putri AR; Sumaryanto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Many MSMEs face obstacles in financial management and product promotion, including Arzzam Tailor, a home business in the sewing service sector. This business does not yet have neat financial records and promotions are still limited, so that business management and development are less than optimal. This community service activity aims to improve managerial skills through simple financial record-keeping training and digital marketing strategies. The methods used include observation, interviews, counseling, and direct training for business owners. The results of the activity show that the owner of Arzzam Tailor is now able to record income and expenses routinely and has started to use social media as a means of promotion. This assistance has a positive impact in helping businesses become more structured and efficient. With good financial records and digital promotion strategies, Arzzam Tailor is better prepared to face challenges and develop its business sustainably in the digital era.